Audit Kinerja Sektor Publik dan Pengawasan Fungsional Terhadap Akuntabilitas Publik Pada Satuan Kerja Perangkat Daerah di Pemerintah Kota Bondowoso - Arik Susbiyani (Jurnal Ilmiah Akuntansi Indonesia, 2017)
This  study  aimed  to  examine:  1)  The effect of performance audit  to  support  public  accountability  on  Bondowoso  government 2) The  effect  of  functional  supervision  to  support  public  accountability  on  Bondowoso  government. This type of research that is classified as causative research. The population in this study is SKPD Bondowoso. The selection of the sample with total sampling method. The data used in this study in the form of primary data. Data collection techniques with survey techniques by distributing questionnaires to each head and the entire head of the SKPD.The research proves that  performance of audit and functional Supervision significant and positive impact on public accountability. In  this study   suggested:  1)  For  a functional  regulatory authorities  in order to  continue to  perform its role  in overseeing the optimal and better  . 2) In the next study  can add variables that affect other Public Accountability such as eksternal control, and supervision of DPRD, Audit performance and Auditor independency .Keywords: performance audit, functional supervision, public accountability